(untitled) - Paul, Rhea. (St. Louis, Mo., 2012)
Language Disorders from Infancy Through Adolescence, 4th Edition is the go-to text for all the information you need to properly assess childhood language disorders and provide appropriate treatment. This core resource spans the entire developmental period through adolescence, and uses a descriptive-developmental approach to present basic concepts and vocabulary, an overview of key issues and controversies, the scope of communicative difficulties that make up child language disorders, and information on how language pathologists approach the assessment and intervention processes. This new edition also features significant updates in research, trends, instruction best practices, and social skills assessment.
Keywords: Language disorders in adolescence,Rối loạn ngôn ngữ ở tuổi vị thành niên